2013
DOI: 10.1086/669087
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Incidence of Carbapenem-Resistant Klebsiella pneumoniae along the Continuum of Care, Los Angeles County

Abstract: CRKP is more present in LAC than suspected. Rates were consistently higher in LTACs than in ACHs. Heightened awareness of this problem is needed in all LAC healthcare facilities, as patients access services along the continuum of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 36 publications
3
35
1
Order By: Relevance
“…Overall, the pooled mean rate is lower than recently reported laboratory-based community-wide surveillance studies from other regions. 28 This is not surprising given a likely publication bias attributable to regions with "hyperendemic" CRE being more likely to publish rates. The fact that Michigan rates are lower than other published rates indicates an opportunity to prevent CRE from becoming hyperendemic in Michigan.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the pooled mean rate is lower than recently reported laboratory-based community-wide surveillance studies from other regions. 28 This is not surprising given a likely publication bias attributable to regions with "hyperendemic" CRE being more likely to publish rates. The fact that Michigan rates are lower than other published rates indicates an opportunity to prevent CRE from becoming hyperendemic in Michigan.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported high incidence rates of CRE in postacute care settings, particularly long-term acute care hospitals. 9,10 Although the study by Guh et al may appear at odds with those other reports, the discrepancy might reflect differences in regional epidemiology that require distinct prevention strategies. Alternatively, the results may be explained by more temporally distant acquisition of CRE by patients; ie, carriage of CRE for more than 3 years after hospital discharge has been reported.…”
Section: 6mentioning
confidence: 83%
“…Consistent with the published literature indicating a higher prevalence of CRKP colonization and dissemination in patients in LTACs compared with those in acute care hospitals, we found that significantly more of the CRKP cohort resided in an SNF/LTAC, whereas the patients in the NRKP cohort were mostly admitted from home. [2][3][4][5][6][7][8]24 With respect to concurrent infections with other pathogens, patients in both groups were equally likely to have polymicrobial primary site infections, but those in the CRKP arm had significantly more concurrent infections at another site other than the primary site of infection. Importantly, patients in the CRKP arm had an up to 37-fold higher risk of having a coinfection with another carbapenem-resistant pathogen (eg, Pseudomonas); this difference was particularly evident in patients with pneumonia.…”
Section: Discussionmentioning
confidence: 99%